Does intellectual capital efficiency matter for banks’ performance and risk-taking behavior? - Changjun Zheng; Md Nazmul Islam; Najmul Hasan; Md. Abdul Halim (Cogent Economics & Finance)
The aim of this study is to investigate whether a bank’s intellectual capital (IC) efficiency impacts its performance and risk-taking behavior in an emerging economic country. The study used panel data (unbalanced) of 30 commercial banks in Bangladesh during 2002–2019. Data were analyzed through the use of the generalized method of moments (GMM) by Eviews-10. The pragmatic results demonstrate that IC efficiency (HCE), RCE and SCE have significant positive (negative) impacts both on the bank’s performance and risk-taking behavior, this finding is similar to resource-based theory. Moreover, adequate capital and liquidity position improves bank performance, but leverage, size, and non-performing loans to total loan have a significant negative impact on bank performance. In addition, the macro-economic variable growth (i.e., gross domestic product) rate of inflation and financial crisis year negatively impacts both bank performance and risk-taking behavior. The panel dataset in this research is restricted to the Bangladeshi banking sector, which restricts the study’s generalizability. Bank performance in Bangladesh is unaffected by leverage, loan size, and the proportion of non-performing loans to total loans. Regulatory authorities, managers and policymakers should step up their surveillance of banks and other financial institutions when the GDP inflation rate and financial crisis year have a negative impact on both bank performance and risk-taking behavior.